A Higher Form of Killing. - Harris, Robert; Paxman, Jeremy (Granada Triad Paladin, 1983)
A Higher Form of Killing opens with the first devastating battlefield use of lethal gas in World War I, and then investigates the stockpiling of biological weapons during World War II and in the decades afterward as well as the inhuman experiments con-ducted to test their effectiveness. This updated edition includes a new Introduction and a new final chapter exposing frightening developments in recent years, including the black market that emerged in chemical and biological weapons following the breakup of the Soviet Union, the acquisition of these weapons by various Third World states, the attempts of countries such as Iraq to build up arsenals, and--particularly and most recently--the use of these weapons in terrorist attacks.
Keywords: Fiction